Die Palastanlage oberhalb des Theaters von Ephesos Planmappe - Baier, Christoph (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
This volume presents the results of the first systematic research of a palatial townhouse in ancient Ephesus from an archaeological and building research perspective. The analysis of the monumental building complex provides fundamental insights into the organisation and diachronic development of the town quarter on the western slope of the Panayırdağ and into the development of palatial architecture in the late Hellenistic and Roman periods. Textband: http://e-book.fwf.ac.at/o:1814 Tafelband: http://e-book.fwf.ac.at/o:1819 Planmappe: http://e-book.fwf.ac.at/o:1821